Industrial design A-Z - Fiell, Charlotte; Fiell, Peter (Koln Taschen, 2003)
For over 200 years, the products or mechanized industrial production have shaped our material culture, influenced world economies and affected the quality of our environment and daily lives. From consumer goods and packaging to transportation systems and production equipment, industrial products encompass an extraordinary range of functions, techniques, attitudes, ideas and values and are a means through which we experience and perceive the world around us.

As more and more countries are drawn into the global free-market economy, so industrial design has become an increasingly vital means of competing on a global scale. By reflecting on the history of industrial design and focusing in particular on its successes, this book hopes to demonstrate how industrial design has consistently sought to de-mystify technology and to deliver it in accessible forms to the greatest number of people.

A further aim of the book is to highlight the phenomenal extent to which manufacturing companies themselves have shaped the history of industrial design. Without their willingness to risk the necessary and sometimes massive investment demanded by the development of new products, there would be very little industrial design. Innovative and commercially-motivated yet socially-minded manufacturing companies are too often the unsung heroes of our material culture.
Donated by Prof. Dante Cruz
Keywords: Industrial design; Industrial arts -- History -- 19th century; Industrial arts -- History -- 20th century; Industrial designers